2021
DOI: 10.1007/978-3-030-85447-8_51
|View full text |Cite
|
Sign up to set email alerts
|

Business Analytics Continuance in Software Development Projects – A Preliminary Analysis

Abstract: This paper investigates factors affecting business analytics (BA) in software and systems development projects. This is the first study to examine business analytics continuance in projects from Pakistani software professional's perspective. The data was collected from 186 Pakistani software professionals working in software and systems development projects. The data was analyzed using partial least squares structural equation modelling techniques. Our structural model is able to explain 40% variance of BA con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 26 publications
1
1
1
Order By: Relevance
“…Surprisingly, BA continuous intention is not affected by perceived usefulness and technological compatibility. Whereas, the literature reported that technological compatibility and perceived usefulness are the key drivers of continuance (Bawack & Ahmad, 2021;Ahmad et al, 2021;Gupta et al, 2020;Grubljesic & Jaklic, 2015;Bhattacherjee, 2001). However, in this study, we observe that technological compatibility and perceived usefulness have no effect on BA continuance in software and system development projects.…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…Surprisingly, BA continuous intention is not affected by perceived usefulness and technological compatibility. Whereas, the literature reported that technological compatibility and perceived usefulness are the key drivers of continuance (Bawack & Ahmad, 2021;Ahmad et al, 2021;Gupta et al, 2020;Grubljesic & Jaklic, 2015;Bhattacherjee, 2001). However, in this study, we observe that technological compatibility and perceived usefulness have no effect on BA continuance in software and system development projects.…”
Section: Discussioncontrasting
confidence: 86%
“…Our findings show that confirmation influence perceived usefulness and technological compatibility as well as confirmation directly influence BA continuous intention. These results are in line with existing studies, which found that such factors are important for BA (Bawack & Ahmad, 2021;Ahmad et al, 2021;Chen et al, 2015;Jaklic et al, 2018;Viaene & Van den Bunder, 2011). On the other hand, technological compatibility and perceived usefulness do not influence the BA continuance.…”
Section: Theoretical Implicationssupporting
confidence: 93%
See 1 more Smart Citation